Laminated Glass
Patent Information
- Application Number
- JP2021574063
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-27
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-01-27
AI Technical Summary
【0026】 本発明により、ミリ波帯の電波の透過性を高めるとともに、本来の合わせガラスとしての強度を満足する合わせガラスを提供できる。
Smart Images

Figure 0007635723000006 
Figure 0007635723000007 
Figure 0007635723000008
Abstract
Description
[Technical field]
[0001] The present invention relates to laminated glass, and in particular to laminated glass for vehicles. [Background technology]
[0002] In recent years, in addition to communications using wavelength bands such as microwaves and millimeter waves, high-speed, large-capacity communications infrastructure such as 4G, LTE, and 5G has expanded, and the frequency bands used tend to expand from the 3 GHz band to the 5-100 GHz band. For example, when transmitting and receiving using millimeter-wave radar installed in a car, radio wave attenuation by window glass, which was not significant in previous frequency band communications (for example, up to 3 GHz), is now an issue.
[0003] As a technique for solving such problems, Patent Document 1 discloses a configuration in which part of window glass, particularly laminated glass for automobiles, is replaced with a radio wave transparent material and fitted in. In other words, Patent Document 1 discloses a configuration in which, in a laminated glass having two pieces of glass and an interlayer film sandwiched between them, a radio wave transparent material is provided in at least the part from which the inner (interior) glass has been removed, in order to increase the radio wave transmission of millimeter wave radar through the window material.
[0004] Furthermore, Patent Document 2 discloses a glass pane that can enhance the detection sensitivity of electromagnetic radiation. The glass pane disclosed in Patent Document 2 enhances the detection sensitivity of electromagnetic radiation that passes through a hole by providing a hole in a part of the inner pane of a composite glass pane (laminated glass). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2017 / 188415 [Patent Document 2] Special Publication No. 2011-502090 Summary of the Invention [Problem to be solved by the invention]
[0006] However, when removing part of the glass to increase the radio wave transmission property of millimeter wave radar and providing a radio wave transmitting material in the area where the glass was removed, as in the window member of Patent Document 1, there was a problem that the manufacturing process became complicated.
[0007] Furthermore, when a hole is provided in part of the inner pane of a composite glass pane (laminated glass) as in Patent Document 2, part of the inner pane is removed, which poses the problem of a reduction in the glass strength required for the composite glass pane (laminated glass).
[0008] In view of the above problems, an object of the present invention is to provide a laminated glass which has improved transmittance for millimeter wave band radio waves and which satisfies the inherent strength required for laminated glass. [Means for solving the problem]
[0009] A laminated glass according to one aspect of the present invention includes a first glass plate, a second glass plate, and an intermediate film sandwiched between the first glass plate and the second glass plate, and a predetermined frequency in the range of 60 GHz to 100 GHz is F [GHz], and a relative dielectric constant of the first glass plate at the frequency F is ε g1 , the relative dielectric constant of the second glass plate is ε g2 The relative dielectric constant of the first intermediate film provided in the first region of the intermediate film is ε m1 When light is incident at the frequency F, the reflection coefficient at the interface between the first glass sheet and the first interlayer film is Γ1, and the reflection coefficient at the interface between the second glass sheet and the first interlayer film is Γ2,
number
[0010] In a plan view of the first glass plate of the laminated glass, the relative dielectric constant of the interlayer at the frequency F is 0.0≦|ε g1 -ε m1 | / ε g1 ≦0.6, 0.0≦|ε g2 -ε m1 | / ε g2 ≦0.6, may be satisfied.
[0011] In the laminated glass, the first interlayer film has the first region and the second region in a plan view of the first glass sheet, and the relative dielectric constant of the second interlayer film provided in the second region at the frequency F is ε m2 Then, ε m2 ≠ε m1 , and |ε g1 -ε m2 | / ε g1 >0.6, |ε g2 -ε m2 | / ε g2 >0.6, may be satisfied.
[0012] In the above laminated glass, the ε m1 , the ε m2 is ε m1 >ε m2 , may be satisfied.
[0013] In the above laminated glass, the ε m1 , the ε m2 is ε m1 -ε m2 ≧1.5 may be satisfied.
[0014] In the above laminated glass, the second interlayer film may contain at least one selected from the group consisting of polyvinyl butyral, ethylene vinyl acetate, cycloolefin polymer, urethane resin, fluorine-based resin, fluororubber, polyimide resin, liquid crystal polymer, bismaleimide triazine resin, polyphenylene ether, polyether terephthalate, acrylic resin such as polymethyl methacrylate resin, silicone resin, ABS resin, Al2O3, and SiO2.
[0015] In the above laminated glass, the ε g1 , the ε g2 , the ε m1 teeth, ε g1 -ε m1 ≦3.5, ε g2 -ε m1 ≦3.5, may be satisfied.
[0016] In the above laminated glass, the first interlayer film may have a visible light transmittance of 70% or more.
[0017] In the above laminated glass, when a radio wave having the frequency F is incident on the first glass plate at an incident angle θ of 30°≦θ≦90°, the first interlayer film has a wavelength of ε m1 But 3≦ε m1 ≦15 may be satisfied.
[0018] In the laminated glass, the frequency F may be 70 GHz to 84 GHz.
[0019] In the above laminated glass, the interlayer film may contain at least one selected from the group consisting of polyvinyl butyral, ethylene vinyl acetate, cycloolefin polymer, urethane resin, and polyvinylidene fluoride resin (PVDF).
[0020] In the above laminated glass, the first interlayer film may contain at least one selected from the group consisting of Al2O3, TiO2, SiO2, ZrO2, YSZ, SnO2, forsterite, cordierite, steatite, barium magnesium niobate, barium neodymium titanate, lead zirconate titanate (PZT), borosilicate glass, alkali-free glass, glass fiber, soda-lime glass, phosphate glass, BaTiO3, SrTiO3, BaSrTiO3, aluminum nitride, and MnO2.
[0021] In the above laminated glass, the first interlayer film may contain Al2O3, and the volume content of Al2O3 may exceed 1.8 vol%.
[0022] In the above laminated glass, the first interlayer film may contain TiO2, and the volume content of the TiO2 may be 0.15 to 3.4 vol %.
[0023] In the above laminated glass, the first interlayer film may contain SiO2, and the volume content of the SiO2 may be 10 vol% or more.
[0024] In the above laminated glass, the first interlayer film has a composition expressed in mole percentage based on oxides, SiO2: 50%~85% B2O3: 0%~35% Al2O3: 0%~25% Li2O+Na2O+K2O: 0%~30% MgO: 0% to 15% CaO: 0% to 15% SrO: 0% to 15% BaO: 0% to 15% ZrO2: 0% to 5% TiO2: 0% to 10% Fe2O3: 0%~5% SnO2: 0% to 5% The glass may contain powdered glass satisfying the above, and the volume content of the glass may be 1 vol % or more and 50 vol % or less.
[0025] In the above laminated glass, the first interlayer film may contain BaTiO3, and the volume content of BaTiO3 may be 1 vol % or more and 50 vol % or less. Effect of the Invention
[0026] The present invention can provide laminated glass that has improved transmittance for millimeter wave band radio waves and that satisfies the inherent strength required for laminated glass. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a diagram showing a vehicle equipped with a laminated glass according to an embodiment. [Figure 2A] FIG. 1 is a perspective view of a laminated glass according to an embodiment. [Figure 2B] FIG. 1 is a perspective view of a laminated glass according to an embodiment. [Diagram 3] FIG. 1 is a cross-sectional view of a laminated glass according to an embodiment. [Figure 4] FIG. 2 is a cross-sectional view for explaining an incident angle θ of a radio wave incident on a laminated glass. [Diagram 5] 1 is a graph showing simulation results of radio wave transmission characteristics of laminated glass. [Figure 6] 1 is a graph showing actual measurement values of radio wave transmission characteristics of laminated glass. [Figure 7] 1 is a graph showing simulation results (εm1≦6.72) of the radio wave transmission characteristics of laminated glass. [Figure 8] 1 is a graph showing simulation results (εm1≧6.72) of the radio wave transmission characteristics of laminated glass. [Figure 9] 1 is a graph showing simulation results (εm1≦6.72) of the radio wave reflection characteristics of laminated glass. [Figure 10] 1 is a graph showing simulation results (εm1≧6.72) of radio wave reflection characteristics of laminated glass. [Figure 11] 1 is a graph showing the simulation results of the radio wave transmission characteristics of laminated glass versus the relative dielectric constant εm1 of the interlayer film. [Figure 12] 1 is a graph showing simulation results of radio wave transmission characteristics of laminated glass (incident angle θ=0° to 30°). [Figure 13] 1 is a graph showing simulation results of radio wave transmission characteristics of laminated glass (incident angle θ=40° to 67.5°). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Fig. 1 is a diagram showing a vehicle equipped with a laminated glass according to the present embodiment. As shown in Fig. 1, the laminated glass 1 according to the present embodiment is typically used as a windshield of a vehicle 100 such as an automobile. However, the laminated glass 1 according to the present embodiment is not limited to the windshield of the vehicle 100, and may also be a rear glass attached to the rear of the vehicle 100, a side glass attached to the side of the vehicle 100, or a roof glass attached to the ceiling of the vehicle 100.
[0029] The vehicle 100 is equipped with an information device for ensuring the driving safety of the vehicle 100. Such an information device is housed, for example, in a housing (case) 10 provided on the vehicle interior side of a laminated glass (windshield) 1. Note that, in FIG. 1, the housing (case) 10 is provided in the upper center of the laminated glass, but the location is not limited to this.
[0030] Here, the information device is a device that detects vehicles, pedestrians, obstacles, etc., present in front of the vehicle using a millimeter wave radar or the like, and may be equipped with a stereo camera, an infrared laser, etc., in addition to the millimeter wave radar. The information device may also include a communication device capable of realizing high-speed, large-capacity communication such as 4G, LTE, and 5G. For example, a communication antenna may be housed in the housing (case) 10.
[0031] In this embodiment, the information device is configured to be capable of transmitting and / or receiving millimeter wave band radio waves (signals). Therefore, in this embodiment, the transmittance of millimeter wave band radio waves can be increased at least at a position of the laminated glass 1 corresponding to the housing (case) 10. In this embodiment, the millimeter wave band is 30 GHz to 300 GHz, and the effect of the present invention is particularly noticeable in the range of 60 GHz to 100 GHz.
[0032] 2A and 2B are perspective views of the laminated glass (front glass) 1 shown in FIG. 1, which are laminated glass 1a and laminated glass 1b, respectively. The laminated glass 1a shown in FIG. 2A is an example in which the first region 21 is an upper region in a plan view of the laminated glass 1a, and the outer edge of the first region 21 is disposed inside the outer edge of the laminated glass 1a. The laminated glass 1b shown in FIG. 2B is an example in which the first region 21 is an upper region in a plan view of the laminated glass 1b, and a part of the outer edge of the first region 21 (here, the upper side) is disposed so as to be shared with a part of the outer edge (here, the upper side) of the laminated glass 1b. The upper side refers to the side that is located on the upper side when the laminated glasses 1a and 1b are installed in a vehicle.
[0033] The structure of the laminated glass 1 (1a, 1b) in the first region 21 will be described below. Note that the laminated glass 1 (1a, 1b) may have all the regions as the first region 21, as described below. In that case, the laminated glass 1 does not have the second region 22.
[0034] Fig. 3 is a cross-sectional view of the laminated glass according to the present embodiment, and is a cross-sectional view taken along the dashed line A-A' of the laminated glass 1a shown in Fig. 2A. As shown in Fig. 3, the laminated glass 1 according to the present embodiment includes a first glass plate 11, a second glass plate 12, and an interlayer film 13 sandwiched between the first glass plate 11 and the second glass plate 12. That is, the first glass plate 11 and the second glass plate 12 are bonded together with the interlayer film 13 interposed therebetween.
[0035] The first glass sheet 11 and the second glass sheet 12 are manufactured by, for example, a float method, a fusion method, or the like, but are not limited to these manufacturing methods. The laminated glass 1 is obtained by laminating the first glass sheet 11, the interlayer film 13, and the second glass sheet 12 in this order, placing them in a vacuum bag such as a rubber bag, connecting the vacuum bag to an exhaust system, and decompressing (degassing) the pressure inside the vacuum bag to a reduced pressure (absolute pressure) of about -65 kPa to -100 kPa, and at a temperature of about 70°C to 110°C. Furthermore, a laminated glass having better durability can be obtained by, for example, performing a pressure bonding treatment in which heating and pressurizing are performed under conditions of a temperature of about 100°C to 140°C and a pressure of 0.6 MPa to 1.3 MPa, but are not limited to this method.
[0036] Furthermore, when the laminated glass 1 is used in, for example, a head-up display (HUD), at least one of the first glass plate 11, the first interlayer film 31, and the second glass plate 12 may have a thickness that is not constant, but may vary from place to place as necessary. For example, when the laminated glass 1 is a windshield, either one or both of the first glass plate 11 and the second glass plate 12 may have a wedge-shaped cross section whose thickness gradually increases from the lower side to the upper side when the windshield is attached to a vehicle. In this case, as long as the thickness of the first interlayer film 31 is constant, the total wedge angle of the glass plate 11 and the glass plate 12 may vary, for example, within a range of more than 0 mrad and not more than 1.0 mrad. Furthermore, when the laminated glass 1 is used in, for example, a HUD, the thickness of the first interlayer film 31 may have a wedge-shaped cross section whose thickness gradually increases from the lower side to the upper side when the windshield is attached to a vehicle. In this case, so long as the thicknesses of the first glass plate 11 and the second glass plate 12 are constant, the wedge angle of the first interlayer film 31 may be changed, for example, within a range of more than 0 mrad to 1.0 mrad or less.
[0037] An example of the composition of at least one of the first glass plate 11 and the second glass plate 12 used in the present embodiment is glass that satisfies the following relationship in terms of a mole percentage based on oxides: Glass containing 50% to 80% SiO2, 0% to 10% B2O3, 0.1% to 25% Al2O3, 3% to 30% in total of at least one alkali metal oxide selected from the group consisting of Li2O, Na2O, and K2O, 0% to 25% MgO, 0% to 25% CaO, 0% to 5% SrO, 0% to 5% BaO, 0% to 5% ZrO2, 0% to 5% Fe2O3, and 0% to 5% SnO2, but is not limited to these compositions.
[0038] Another example of the composition of at least one of the first glass plate 11 and the second glass plate 12 used in this embodiment may be glass whose composition, expressed in terms of oxide-based mole percentage, satisfies the following relationship: 50≦SiO2≦85 0≦Al2O3≦20 4≦R2O≦22 (R2O represents the total amount of alkali metal oxides) 0≦RO≦20 (RO represents the total amount of MgO, CaO, SrO, and BaO) 0≦Na2O / R2O≦0.8 0≦K2O / R2O≦0.7
[0039] Another example of the composition of at least one of the first glass plate 11 and the second glass plate 12 used in the present embodiment may be glass whose composition is expressed in terms of oxide-based mole percentage and which satisfies the following relationship: 72≦SiO2+Al2O3+B2O3≦98 55≦SiO2≦87 0≦Al2O3≦20 0≦B2O3≦25 0≦R2O≦5 (R2O represents the total amount of alkali metal oxides) 0≦RO≦20 (RO represents the total amount of MgO, CaO, SrO, and BaO)
[0040] In addition, in the laminated glass 1a shown in FIG. 3, the interlayer film 13 includes a first interlayer film 31 disposed in the first region 21 and a second interlayer film 32 disposed in the second region 22. The first interlayer film 31 has a relative dielectric constant of ε m1 The second intermediate film 32 is made of a material having a relative dielectric constant of ε m2 is the material.
[0041] The interlayer film 13 may be made of a material including, for example, polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), cycloolefin polymer, urethane resin, polyvinylidene fluoride resin (PVDF), etc. Alternatively, a thermosetting resin that is liquid before heating may be used. That is, the interlayer film 13 may be in a layered form when the laminated glass 1 is formed, and may be liquid before the first glass plate 11 and the second glass plate 12 are bonded together. Details of the interlayer film 13 will be described later.
[0042] The specific configuration of the laminated glass 1 according to this embodiment and the results of simulation will be described in detail below.
[0043] As shown in Fig. 3, the laminated glass 1 according to the present embodiment includes a first glass plate 11, a second glass plate 12, and an interlayer film 13 sandwiched between the first glass plate 11 and the second glass plate 12. The laminated glass 1 according to the present embodiment has a specific frequency F [GHz] in the range of 60 GHz to 100 GHz, and the relative dielectric constant of the first glass plate at frequency F is ε g1 , the relative dielectric constant of the second glass plate is ε g2 , the relative dielectric constant of the first intermediate film 31 is ε m1 When light is incident at a frequency F, the reflection coefficient at the interface between the first glass plate 11 and the first intermediate film 31 is Γ1, and the reflection coefficient at the interface between the second glass plate 12 and the first intermediate film 31 is Γ2. The following equations 1 to 3 are satisfied.
[0044]
number
[0045] In this embodiment, the relative dielectric constants of the elements constituting the laminated glass 1 are set to have the above-mentioned relationship, so that the relative dielectric constant difference between the first glass sheet 11 and the first interlayer film 31 and the relative dielectric constant difference between the second glass sheet 12 and the first interlayer film 31 can be reduced. In this way, when the relative dielectric constant difference between the first glass sheet 11 and the second glass sheet 12 and the interlayer film 13 (first interlayer film 31) is reduced, reflection at the interface between the first glass sheet 11 and the second glass sheet 12 and the interlayer film 13 (first interlayer film 31) can be suppressed, so that the transmittance of millimeter wave band radio waves can be improved. In addition, the relative dielectric constant difference between the first glass sheet 11 and the first interlayer film 31 and the relative dielectric constant difference between the second glass sheet 12 and the first interlayer film 31 may be 0.15 or less, preferably 0.12 or less, more preferably 0.09 or less, even more preferably 0.06 or less, particularly preferably 0.03 or less, and most preferably 0.01 or less.
[0046] Furthermore, in this embodiment, there is no need to remove some of the elements constituting the laminated glass 1, particularly some of the first glass plate 11 and the second glass plate 12, and therefore the strength required for laminated glass is sufficient. That is, the laminated glass 1 according to this embodiment has a three-layer structure of the first glass plate 11, the second glass plate 12, and the interlayer film 13, and therefore the strength required for laminated glass is sufficient.
[0047] Here, the first region 21 corresponds to a region including at least a position corresponding to a housing 10 (see FIG. 1) in which an information device is housed, in a plan view of the first glass plate 11. Specifically, the laminated glass 1 only needs to include a first interlayer film 31 having a configuration according to the present embodiment at least in a position corresponding to the housing 10 (see FIG. 1), that is, in a position (first region 21) where a millimeter wave radar travels through the window glass 1. The interlayer film provided in a region other than the region including the position corresponding to the housing 10 may be the first interlayer film 31 or the second interlayer film, and may be configured as desired.
[0048] In the present embodiment, in the first region 21 of the first glass plate 11 in a plan view, the relative dielectric constant of the first interlayer film 31 at frequency F may satisfy the following formulas 4 and 5. By satisfying such conditions, the transmittance of millimeter-wave band radio waves can be increased.
[0049] 0.0≦|ε g1 -ε m1 | / ε g1 ≦0.6 ···Equation 4 0.0≦|ε g2 -ε m1 | / ε g2 ≦0.6...Equation 5
[0050] Furthermore, in this embodiment, the relative dielectric constant ε g1 , the relative dielectric constant ε of the second glass plate 12 g2 , the relative dielectric constant ε of the first intermediate film 31 m1 However, the following formulas 6 and 7 may be satisfied. By satisfying these conditions, the transmittance of millimeter wave band radio waves can be increased.
[0051] ε g1 -ε m1 ≦3.5...Equation 6 ε g2 -ε m1 ≦3.5...Equation 7
[0052] The first intermediate film 31 may also have a visible light transmittance of 70% or more. By satisfying such conditions, the transmittance of millimeter wave band radio waves in the first region 21 is increased, and the transmittance of visible light is also increased. In particular, when an imaging device that captures images outside the vehicle is also provided inside the housing 10, it is preferable that the first intermediate film has a high visible light transmittance. The visible light transmittance of the first intermediate film is preferably 75% or more, more preferably 80% or more, even more preferably 85% or more, and most preferably 90% or more.
[0053] The first intermediate film 31 may be made of a material having a dielectric loss tangent (tan δ) of 0.01 or less at frequency F. Such a configuration further enhances the transmittance of millimeter wave band radio waves in the first region 21. The first intermediate film 31 has a dielectric loss tangent at frequency F of preferably 0.008 or less, more preferably 0.005 or less, further preferably 0.003 or less, and particularly preferably 0.001 or less.
[0054] Furthermore, the first glass plate 11 and the second glass plate 12 may be made of a material having a dielectric tangent (tan δ) of 0.025 or less at frequency F. Such a configuration further enhances the transmittance of millimeter wave band radio waves in the first region 21. Furthermore, the dielectric tangent of the first glass plate 11 and the second glass plate 12 at frequency F is preferably 0.020 or less, more preferably 0.018 or less, further preferably 0.015 or less, and particularly preferably 0.012 or less.
[0055] The first glass plate 11 and the second glass plate 12 may be made of a material having a relative dielectric constant of 3.5 or more at frequency F. This configuration further enhances the transmittance of millimeter-wave radio waves in the first region 21. The first glass plate 11 and the second glass plate 12 preferably have a relative dielectric constant of 4.5 or more at frequency F, more preferably 5.5 or more, and even more preferably 6.0 or more. On the other hand, if the first glass plate 11 and the second glass plate 12 have a too high relative dielectric constant, the reflection of radio waves at frequency F increases and the transmittance decreases, so the relative dielectric constant may be 8.0 or less, preferably 7.0 or less, more preferably 6.5 or less, and even more preferably 6.1 or less.
[0056] When a radio wave having a frequency F is incident on the first glass plate 11 at an incident angle θ (θ is 30°≦θ≦90°), the first intermediate film 31 has a relative dielectric constant ε m1 But 3≦ε m1 For example, when a millimeter wave is emitted from a millimeter wave radar emitting device attached to the housing 10 in the horizontal direction, the relative dielectric constant εm1 It is preferable that the relative dielectric constant ε satisfies the above range when the incident angle θ is in the range of 40°≦θ≦80°. m1 may satisfy the above range, and the relative dielectric constant ε in the range of 50°≦θ≦75° m1 may satisfy the above range, and the relative dielectric constant ε in the range of 60°≦θ≦75° m1 may satisfy the above range.
[0057] In addition, in this embodiment, the frequency F may be, for example, in the range of 60 GHz to 100 GHz, or further in the range of 70 GHz to 84 GHz, or in the range of 74 GHz to 82 GHz, or in the range of 77 GHz to 81 GHz, or in the range of 78.5 GHz to 79.5 GHz, or more specifically, may be 79 GHz.
[0058] In the present embodiment, the first intermediate film 31 may contain at least one selected from the group consisting of polyvinyl butyral, ethylene vinyl acetate, cycloolefin polymer, urethane resin, and further, fluorine-based resins such as polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (ETFE), perfluoroalkoxyalkane (PFA), and polyvinylidene fluoride (PVDF), fluorine-containing rubber, polyimide resin, liquid crystal polymer (LCP), bismaleimide triazine resin, polyphenylene ether (PPE), polyether terephthalate (PET), acrylic resins such as polymethyl methacrylate resin, silicone resin, ABS resin, Al2O3, and SiO2.
[0059] In the present embodiment, the first intermediate film 31 may contain an adhesive or a pressure-sensitive adhesive. For example, the first intermediate film 31 may be one in which an adhesive or a pressure-sensitive adhesive is disposed on at least one of the main surface in contact with the first glass plate 11 and the main surface in contact with the second glass plate 12. For example, the adhesive layer included in the first intermediate film 31 and in contact with at least one of the first glass plate 11 and the second glass plate 12 may be obtained by curing a photocurable resin composition, a thermosetting resin composition, a photo- and thermosetting resin composition, or the like. The term "photocurable resin composition" refers to a resin composition that can be cured by exposure to light. The term "thermosetting resin composition" refers to a resin composition that can be cured by heating. The term "photo- and thermosetting resin composition" refers to a resin composition that can be cured by exposure to light and heating.
[0060] The first intermediate film 31 may contain a high dielectric constant filler in the resin material to adjust the relative dielectric constant. For example, the first intermediate film 31 may contain, as a filler, at least one selected from the group consisting of Al2O3, TiO2, SiO2, ZrO2, YSZ (Yttria-Stabilized Zirconia), SnO2, forsterite, cordierite, steatite, barium magnesium niobate, barium neodymium titanate, lead zirconate titanate (PZT), (powdered) borosilicate glass, (powdered) alkali-free glass, glass fiber (E glass, D glass, NE glass, etc.), (powdered) soda lime glass, (powdered) phosphate glass, BaTiO3, SrTiO3, BaSrTiO3, aluminum nitride, and MnO2 in polyvinyl butyral, ethylene vinyl acetate, etc.
[0061] For example, when the first intermediate film 31 contains powdered Al2O3, the volume content of Al2O3 may be 1.8 vol% or more, preferably 2.3 vol% or more, and more preferably 3.0 vol% or more. Although it depends on the (resin) material that is the main component constituting the first intermediate film 31, if the volume content of Al2O3 is less than 1.8 vol%, the relative dielectric constant ε of the (filler-containing) first intermediate film 31 becomes m1 It is difficult to increase the dielectric constant.
[0062] Furthermore, when the first intermediate film 31 contains powdered TiO2, the volume content of TiO2 may be 0.15 vol% or more, preferably 0.20 vol% or more, and more preferably 0.30 vol% or more. Although it depends on the (resin) material that is the main component constituting the first intermediate film 31, if the volume content of TiO2 is less than 0.15 vol%, the relative dielectric constant ε of the first intermediate film 31 (containing filler) m1 In addition, although it depends on the (resin) material that is the main component constituting the first intermediate film 31, the volume content of TiO2 is preferably 3.4 vol% or less, more preferably 3.0 vol% or less, and more preferably 2.5 vol% or less. If the volume content of TiO2 exceeds 3.4 vol%, the relative dielectric constant ε m1 If this becomes too high, there is a risk that reflection at the interface between the first interlayer film 31 and the glass plate 11 and at the interface between the first interlayer film 31 and the glass plate 12 will be large.
[0063] Furthermore, when the first intermediate film 31 contains powdered SiO2, the volume content of SiO2 may be 10 vol% or more, preferably 20 vol% or more, and more preferably 30 vol% or more. Although it depends on the (resin) material that is the main component constituting the first intermediate film 31, if the volume content of SiO2 is less than 10 vol%, the relative dielectric constant ε of the (filler-containing) first intermediate film 31 becomes m1 It is difficult to raise the price.
[0064] When the first intermediate film 31 contains powdered glass, the composition of the first intermediate film 31 is expressed in mole percentage based on oxides, and is as follows: SiO2: 50%~85% B2O3: 0%~35% Al2O3: 0%~25% Li2O+Na2O+K2O: 0%~30% MgO: 0% to 15% CaO: 0% to 15% SrO: 0% to 15% BaO: 0% to 15% ZrO2: 0% to 5% TiO2: 0% to 10% Fe2O3: 0%~5% SnO2: 0% to 5% The volume content of the powdered glass can be adjusted to be in the range of 1 vol% to 50 vol%. Although it depends on the (resin) material that is the main component constituting the first intermediate film 31, if the volume content of the powdered glass is less than 1 vol%, the relative dielectric constant ε of the (filler-containing) first intermediate film 31 becomes m1 Moreover, if the volume content of the powdered glass exceeds 50 vol %, the first interlayer film 31 tends to become brittle.
[0065] In addition, when powdered glass is included, the composition expressed in mole percentage based on oxides is: SiO2: 60%~85% B2O3: 0% to 15% Al2O3: 0% to 10% Li2O+Na2O+K2O: 0%~20% MgO: 0% to 10% CaO: 0% to 10% SrO: 0% to 10% BaO: 0% to 10% ZrO2: 0% to 3% TiO2: 0% to 5% Fe2O3: 0%~2% SnO2: 0% to 3% In this case, the volume content of the powdered glass can be adjusted within the range of 1 vol % to 50 vol %.
[0066] Furthermore, when the first intermediate film 31 contains BaTiO3 (powder), the volume content of the powdered BaTiO3 can be adjusted to a range of 10 vol% to 50 vol%. Although it depends on the (resin) material that is the main component constituting the first intermediate film 31, if the volume content of the powdered BaTiO3 is less than 1 vol%, the relative dielectric constant ε of the first intermediate film 31 (containing filler) m1 Moreover, if the volume content of powdered BaTiO3 exceeds 50 vol %, the first intermediate film 31 tends to become brittle.
[0067] The shape of these fillers is not particularly limited, and examples of the shapes include those seen in powder, such as spheres, crushed shapes (block shapes), flat shapes, and columnar shapes. However, the shape of the fillers is not limited to these, and they may also be short fibers (chopped strands), long fibers, ultrafine fibers, hollow fibers, or glass cloth shapes. For example, when the fillers are spherical, their size may be 100 μmφ or less.
[0068] In addition, when the interlayer film 13 has a first region 21 and a second region 22 in a plan view of the first glass plate 11, the relative dielectric constant ε of the second interlayer film 32 disposed in the second region 22 at a frequency F is m2 is ε m2 ≠ε m1 and may satisfy the following formulas 8 and 9. Here, the plan view refers to the case where the laminated glass 1 is viewed from the plate thickness direction.
[0069] |ε g1 -ε m2 | / ε g1 >0.6...Equation 8 |ε g2 -ε m2 | / ε g2 >0.6...Equation 9
[0070] In this embodiment, the relative dielectric constant ε of the first intermediate film 31 m1 and the relative dielectric constant ε of the second intermediate film 32 m2 And, ε m1 >ε m2 Furthermore, in this embodiment, the relative dielectric constant ε of the first intermediate film 31 may be m1 and the relative dielectric constant ε of the second intermediate film 32 m2 And, ε m1 -ε m2 ≧1.5, and ε m1 -ε m2 ≧2.0, and ε m1 -ε m2 ≧2.5, and ε m1 -ε m2 ≧3.0, and ε m1 -ε m2In this way, the relative dielectric constant ε of the first intermediate film 31 may be ≧3.5. m1 and the relative dielectric constant ε of the second intermediate film 32 m2 By satisfying the above-mentioned conditions, the transmittance of millimeter wave band radio waves in the first region of the laminated glass can be selectively increased.
[0071] In the present embodiment, the second intermediate film 32 may contain at least one selected from the group consisting of polyvinyl butyral, ethylene vinyl acetate, cycloolefin polymer, urethane resin, and polyvinylidene fluoride resin (PVDF).
[0072] In this embodiment, as described above, in the entire laminated glass (front glass) 1 shown in FIG. 1, the relative dielectric constant of the interlayer 13 is set to ε m1 In other words, the entire interlayer film 13 of the laminated glass (front glass) 1 shown in FIG.
[0073] In the present embodiment, the thickness of the first glass plate 11 and the second glass plate 12 is 1.1 mm or more to ensure strength, preferably 1.5 mm or more, and more preferably 1.8 mm or more. Although there is no particular upper limit to the thickness of the first glass plate 11 and the second glass plate 12, the weight increases as the thickness increases, so that the thickness is usually desirably 3.0 mm or less.
[0074] From the viewpoint of ease of handling, the thickness of the intermediate film 13 is preferably 0.3 mm or more, more preferably 0.5 mm or more, and even more preferably 0.7 mm or more, and from the viewpoint of light weight, the thickness is preferably 2.3 mm or less, more preferably 2.0 mm or less, and even more preferably 1.0 mm or less.
[0075] (Simulation results) Next, a simulation result of the laminated glass 1 according to the present embodiment will be described. FIG. 4 is a cross-sectional view for explaining the incident angle θ of a radio wave incident on the laminated glass. As shown in FIG. 4, the incident angle θ is the angle between a line segment 15 perpendicular to the main surface of the laminated glass and the traveling direction of the radio wave (x-axis direction). Note that the laminated glass 1 shown in FIG. 4 is a schematic diagram in which only the first region 21 is extracted, but it may also have a second region 22 (not shown). FIG. 5 is a graph showing a simulation result of the radio wave transmission characteristics of the laminated glass. The conditions for the simulation shown in FIG. 5 are as follows.
[0076] In Example 1, the relative dielectric constant of the first intermediate film 31 in FIG. m1 The relative dielectric constant of the first intermediate film 31 in Comparative Examples 1 and 2 was ε m1 The relative dielectric constant of the first glass plate 11 was set to ε g1 = 6.72, and the relative dielectric constant of the second glass plate 12 is ε g2 = 6.72. Each dielectric constant is the dielectric constant at a frequency F of 79 GHz. The thickness of each of the first glass plate 11 and the second glass plate 12 was 2 mm, and the thickness of the first intermediate film 31 was 0.76 mm. The frequency range of the millimeter wave radio waves in the simulation was 70 GHz to 84 GHz.
[0077] In the simulation conditions shown in FIG. 5, the incident angle θ of the radio wave in Example 1 was θ=67.5°. The incident angle θ in Comparative Example 1 was θ=67.5°, and the incident angle θ in Comparative Example 2 was θ=0°, that is, perpendicular incidence with respect to the main surface of the laminated glass 1. In the simulation results shown below (FIGS. 5 to 12), vertically polarized waves were used as the radio waves incident on the laminated glass 1. Specifically, the vertically polarized waves are polarized waves (TM waves) whose electric field components are oriented in the z-axis direction in the cross-sectional view shown in FIG. 4. The horizontally polarized waves are polarized waves (TE waves) whose electric field components are oriented in the y-axis direction in the cross-sectional view shown in FIG. 4.
[0078] The results of simulating the radio wave transmission characteristics (S21) using these conditions are shown in Figure 5. Note that in the simulation results of the radio wave transmission characteristics, the higher the value of S21 [dB], the better the radio wave transmission.
[0079] As shown in FIG. 5, the first intermediate film 31 has a relative dielectric constant of ε m1 = 2.45 (Comparative Example 1), the radio wave transmission characteristic was about -3 dB. m1 = 6.15 (Example 1), the radio wave transmission characteristic was improved to about -2 dB. m1 = 6.15 is better than ε m1 The radio wave transmission characteristics were better than when = 2.45.
[0080] In other words, the relative dielectric constant of the first intermediate film 31 is ε m1 In the case where the dielectric constant of the first interlayer 31 is 6.15, the dielectric constant of the first glass sheet 11 and the dielectric constant of the second glass sheet 12 (ε g1 ,ε g2 : 6.72). Therefore, reflection at the interfaces between the first glass plate 11 and the second glass plate 12 and the first intermediate film 31 can be suppressed, and the transmittance of millimeter-wave radio waves can be improved. In Comparative Example 2 with the incident angle θ = 0°, the radio wave transmission characteristics varied depending on the frequency of the radio waves, and in the range of 70 GHz to 77 GHz, the radio wave transmission characteristics were -4 dB or less.
[0081] Next, the radio wave transmission characteristics of the laminated glass 1 were measured to verify the relationship with the simulation results shown in Fig. 5. Fig. 6 is a graph showing the actual measured values of the radio wave transmission characteristics of the laminated glass (S21: unit [dB]), which were measured under the following measurement conditions.
[0082] The relative dielectric constant of the first intermediate film 31 is ε m1 = 6.15, ε m1 The relative dielectric constant of the first glass plate 11 was set to ε g1 = 6.72, and the relative dielectric constant of the second glass plate 12 is ε g2= 6.72. Each dielectric constant is the dielectric constant at a frequency F = 79 GHz.
[0083] The first glass plate 11 and the second glass plate 12 were made of glass having the following composition, expressed as mole percentages based on the oxide of each component: SiO2: 69.7%, Al2O3: 0.9%, MgO: 7%, CaO: 9%, TiO2: 0.05%, Na2O: 12.6%, K2O: 0.6%, and Fe2O3: 0.2%. The first glass plate 11 and the second glass plate 12 were glasses corresponding to "Composition Example 1" in Table 1.
[0084] [Table 1]
[0085] For the first intermediate film 31, a material mainly composed of PTFE (RF-60TC (manufactured by KOREA TACONIC): dielectric constant at 10 GHz = 6.40, tan δ at 10 GHz = 0.002) was used as Example 1, and polyvinyl butyral (PVB) (dielectric constant at 10 GHz = 2.60) was used as Comparative Example 1. The dielectric constant and dielectric loss tangent (tan δ) of the first intermediate film 31 at 10 GHz were measured by a split post dielectric resonator (SPDR) method in an environment within the range of 23°C ± 2°C and 50 ± 5% RH.
[0086] Here, the materials of Example 1 and Comparative Example 1 have a tendency that the dielectric constant decreases as the frequency band increases. Therefore, the first intermediate film 31 mainly composed of PTFE in Example 1 has a dielectric constant of ε at 79 GHz based on the measured value of 6.40 at 10 GHz. m1 Further, the first intermediate film 31 (PVB) in Comparative Example 1 has a relative dielectric constant of ε = 6.15 at 79 GHz based on the measured value of 2.60 at 10 GHz. m1= 2.45. The thicknesses of the first glass plate 11 and the second glass plate 12 were each 2 mm, and the thickness of the first interlayer film 31 was 0.76 mm. The frequency of the radio waves used in the measurements was in the range of 70 GHz to 84 GHz. The incident angle θ of the radio waves was θ = 67.5°.
[0087] As shown in FIG. 6, the relative dielectric constant of the intermediate film 13 is ε m1 = 2.45 (Comparative Example 1), the radio wave transmission characteristic was about -3 dB. m1 = 6.15 (Example 1), the radio wave transmission characteristic was about -2 dB. m1 = 6.15 is better than ε m1 = 2.45, the radio wave transmission characteristics are better than that in the case of ε m1 = 2.45 and ε m1 = 6.15, the simulation results (FIG. 5) and the actual measurements (FIG. 6) were close to each other. Therefore, the simulation results in this embodiment correspond to the actual measurements and can be said to be almost accurate.
[0088] Next, the relative dielectric constant ε of the first intermediate film 31 m1 7 is a graph showing the results of a simulation of the radio wave transmission characteristics of the laminated glass 1. In the graph, the relative dielectric constant of the first interlayer 31 is ε m1 8 is a graph showing the simulation results of the radio wave transmission characteristics of the laminated glass 1, in which the relative dielectric constant of the first interlayer film 31 is ε m1 ≧6.72. Note that in the simulation results for the radio wave transmission characteristics, the higher the S21 [dB] value, the better the radio wave transmission.
[0089] The conditions for the simulation shown in FIGS. In the simulation shown in FIG. 7, the relative dielectric constant ε m1was set to 2.8, 3, 3.5, 4.5, 5.5, 6.15, and 6.72. In the simulation shown in FIG. 8, the relative dielectric constant ε m1 was 6.72, 8, 10, 13, 15, 18, and 20. The relative dielectric constants of the first intermediate film 31 in Comparative Examples 1 and 2 were ε m1 The relative dielectric constant of the first glass plate 11 was set to ε g1 = 6.72, and the relative dielectric constant of the second glass plate 12 is ε g2 = 6.72. Each dielectric constant is a dielectric constant at a frequency F of 79 GHz. The thickness of each of the first glass plate 11 and the second glass plate 12 was 2 mm, and the thickness of the intermediate film 13 was 0.76 mm. The frequency range in the simulation was 70 GHz to 84 GHz. The incident angle θ of the radio wave in Comparative Example 1 was θ = 0°, and for the other comparative examples (including Comparative Example 2), the incident angle θ of the radio wave was θ = 67.5°.
[0090] First, the simulation results shown in FIG. 7, that is, the relative dielectric constant of the first intermediate film 31 is ε m1 7, the case where the relative dielectric constant of the first intermediate film 31 is ε m1 In Comparative Example 2, where the relative dielectric constant ε m1 As the relative dielectric constant ε of the first intermediate film 31 increased, the radio wave transmission characteristics improved. m1 As the relative dielectric constant of the first intermediate film 31 increases in the order of 3.0, 3.5, 4.5, and 5.5, the radio wave transmission characteristics improve. m1 The best radio wave transmission characteristics were observed when the value was 6.72.
[0091] In other words, the relative dielectric constant of the first intermediate film 31 is ε m1 = 6.72, the relative dielectric constant of the first intermediate film 31 approaches the relative dielectric constant (6.72) of the first glass sheet 11 and the second glass sheet 12. m1= 6.72, the difference in relative dielectric constant between the first glass plate 11 and the first interlayer film 31 and the difference in relative dielectric constant between the second glass plate 12 and the first interlayer film 31 become small, so that it is possible to suppress the reflection of radio waves at the interfaces between the first glass plate 11 and the second glass plate 12 and the first interlayer film 31. Therefore, the transmittance of radio waves in the millimeter wave band can be improved. In Comparative Example 1 where the incident angle θ = 0°, the radio wave transmission characteristics vary depending on the frequency of the radio waves, and in the range of 70 GHz to 78 GHz, the radio wave transmission characteristics were -3.5 dB or less.
[0092] Here, the reflection coefficients Γ1 and Γ2 can be calculated using the above formula 1 as follows. Note that under the conditions of the above simulation, ε g1 =ε g2 = 6.72, so the values of Γ1 and Γ2 are the same.
[0093] The relative dielectric constant ε of the first intermediate film 31 m1 When is 2.8, Γ1, Γ2 = 0.215. The relative dielectric constant ε of the first intermediate film 31 m1 When is 3, Γ1, Γ2 = 0.199. The relative dielectric constant ε of the first intermediate film 31 m1 When is 3.5, Γ1, Γ2 = 0.162. The relative dielectric constant ε of the first intermediate film 31 m1 When is 4.5, Γ1, Γ2 = 0.100. The relative dielectric constant ε of the first intermediate film 31 m1 When is 5.5, Γ1, Γ2 = 0.050. The relative dielectric constant ε of the first intermediate film 31 m1 When is 6.15, Γ1, Γ2 = 0.022. The relative dielectric constant ε of the first intermediate film 31 m1 If is 6.72, then Γ1, Γ2 = 0.
[0094] From the above results, the relative dielectric constant ε m1 is 3.0 or more, the conditions of the above formulas 2 and 3 are satisfied.
[0095] In addition, taking the above simulation results into consideration, the relative dielectric constant ε m1is preferably in the range of 3.5 or more, and in this case, the ranges of the above formulas 2 and 3 are 0.0≦Γ1≦0.162 and 0.0≦Γ2≦0.162, respectively. In addition, taking the above simulation results into consideration, the relative dielectric constant ε m1 is more preferably in the range of 4.5 or more, and in this case, the ranges of the above formulas 2 and 3 are 0.0≦Γ1≦0.100 and 0.0≦Γ2≦0.100, respectively. In addition, taking the above simulation results into consideration, the relative dielectric constant ε m1 is more preferably in the range of 5.5 or more, and in this case, the ranges of the above formulas 2 and 3 are 0.0≦Γ1≦0.050 and 0.0≦Γ2≦0.050, respectively.
[0096] Next, the simulation results shown in FIG. 8, that is, the relative dielectric constant of the first intermediate film 31 is ε m1 ≧6.72 (excluding Comparative Examples 1 and 2). As shown in FIG. 8, when the relative dielectric constant of the first intermediate film 31 is ε m1 In Comparative Example 2, where the relative dielectric constant of the first intermediate film 31 is large, ε m1 = 18 (Comparative Example 3), ε m1 = 20 (Comparative Example 4), the radio wave transmission characteristics were also poor. m1 As the relative dielectric constant ε of the intermediate film 13 becomes smaller than 18, the radio wave transmission characteristics improve. m1 The radio wave transmission characteristics improved as the relative dielectric constant of the first intermediate film 31 decreased in the order of 15, 13, 10, and 8. m1 The best radio wave transmission characteristics were observed when the value was 6.72.
[0097] In other words, the relative dielectric constant of the first intermediate film 31 is ε m1 = 6.72, the relative dielectric constant of the first intermediate film 31 approaches the relative dielectric constant (6.72) of the first glass sheet 11 and the second glass sheet 12. m1= 6.72, the difference in relative dielectric constant between the first glass plate 11 and the first interlayer film 31 and the difference in relative dielectric constant between the second glass plate 12 and the first interlayer film 31 become small, so that it is possible to suppress the reflection of radio waves at the interfaces between the first glass plate 11 and the second glass plate 12 and the first interlayer film 31. Therefore, the transmittance of radio waves in the millimeter wave band can be improved. In Comparative Example 1 where the incident angle θ = 0°, the radio wave transmission characteristics vary depending on the frequency of the radio waves, and in the range of 70 GHz to 78 GHz, the radio wave transmission characteristics were -3.5 dB or less.
[0098] Here, the reflection coefficients Γ1 and Γ2 can be calculated using the above formula 1 as follows. Note that under the conditions of the above simulation, ε g1 =ε g2 = 6.72, so the values of Γ1 and Γ2 are the same.
[0099] The relative dielectric constant ε of the first intermediate film 31 m1 When is 20, Γ1, Γ2 = 0.266. The relative dielectric constant ε of the first intermediate film 31 m1 When is 18, Γ1, Γ2 = 0.241. The relative dielectric constant ε of the first intermediate film 31 m1 When is 15, Γ1, Γ2 = 0.198. The relative dielectric constant ε of the first intermediate film 31 m1 When is 13, Γ1, Γ2 = 0.163. The relative dielectric constant ε of the first intermediate film 31 m1 When is 10, Γ1, Γ2 = 0.099. The relative dielectric constant ε of the first intermediate film 31 m1 When is 8, Γ1, Γ2 = 0.046. The relative dielectric constant ε of the first intermediate film 31 m1 If is 6.72, then Γ1, Γ2 = 0.
[0100] From the above results, the relative dielectric constant ε m1 When is 15 or less, the above conditions of formula 2 and formula 3 are satisfied.
[0101] In addition, taking the above simulation results into consideration, the relative dielectric constant ε m1is preferably in the range of 13 or less, and in this case, the ranges of the above formulas 2 and 3 are 0.0≦Γ1≦0.163 and 0.0≦Γ2≦0.163, respectively. Furthermore, taking the above simulation results into consideration, the relative dielectric constant ε m1 is more preferably 10 or less, and in this case, the ranges of the above formulas 2 and 3 are 0.0≦Γ1≦0.099 and 0.0≦Γ2≦0.099, respectively. Furthermore, taking the above simulation results into consideration, the relative dielectric constant ε m1 is more preferably equal to or less than 8, and in this case, the ranges of the above formulas 2 and 3 are 0.0≦Γ1≦0.046 and 0.0≦Γ2≦0.046, respectively.
[0102] From the simulation results shown in FIGS. 7 and 8, the relative dielectric constant ε m1 The range of ε is 3≦ε m1 ≦15, preferably 3.5≦ε m1 ≦13, more preferably 4.5≦ε m1 ≦10, more preferably 5.5≦ε m1 When the ratio is ≦8, the laminated glass can be said to have good radio wave transmission properties.
[0103] Next, the relationship between the relative dielectric constant of the first interlayer film 31 and the radio wave reflection characteristics will be described. Fig. 9 is a graph showing the simulation results of the radio wave reflection characteristics of the laminated glass 1. In Fig. 9, the relative dielectric constant of the first interlayer film 31 is ε m1 10 is a graph showing the simulation results of the radio wave reflection characteristics of laminated glass, in which the relative dielectric constant of the first interlayer 31 is ε m1 ≧6.72. Note that in the simulation results for radio wave reflection characteristics, the lower the S11 [dB] value, the less radio waves are reflected, and therefore the better the radio wave transmission.
[0104] The conditions for the simulation shown in FIGS. 9 and 10 are as follows: In the simulation shown in FIG. 9, the relative dielectric constant ε m1was set to 2.8, 3, 3.5, 4.5, 5.5, 6.15, and 6.72. In the simulation shown in FIG. 10, the relative dielectric constant ε m1 was 6.72, 8, 10, 13, 15, 18, and 20. The relative dielectric constants of the first intermediate film 31 in Comparative Examples 1 and 2 were ε m1 The relative dielectric constant of the first glass plate 11 was set to ε g1 = 6.72, and the relative dielectric constant of the second glass plate 12 is ε g2 = 6.72. Each dielectric constant is a dielectric constant at a frequency F of 79 GHz. The thickness of each of the first glass plate 11 and the second glass plate 12 was 2 mm, and the thickness of the first interlayer film 31 was 0.76 mm. The frequency range in the simulation was 70 GHz to 84 GHz. The incident angle θ of the radio wave in Comparative Example 1 was θ = 0°, and for the other comparative examples, the incident angle θ of the radio wave was θ = 67.5°.
[0105] First, the simulation results shown in FIG. 9, that is, the relative dielectric constant of the first intermediate film 31 is ε m1 9, the case where the relative dielectric constant of the first intermediate film 31 is ε m1 In Comparative Examples 1 and 2, where the relative dielectric constant ε m1 When the relative dielectric constant ε of the first intermediate film 31 is 2.8 or more, m1 As the relative dielectric constant ε of the first intermediate film 31 increased, the radio wave reflection characteristics improved (decreased). m1 As the relative dielectric constant of the first intermediate film 31 increases in the order of 3.0, 3.5, 4.5, and 5.5, the radio wave reflection characteristics improve (deteriorate). m1 The radio wave reflection characteristics were the lowest when = 6.72.
[0106] In other words, the relative dielectric constant of the first intermediate film 31 is ε m1 = 6.72, the relative dielectric constant of the first intermediate film 31 approaches the relative dielectric constant (6.72) of the first glass sheet 11 and the second glass sheet 12. m1= 6.72, the difference in relative dielectric constant between the first glass plate 11 and the first interlayer film 31 and the difference in relative dielectric constant between the second glass plate 12 and the first interlayer film 31 become small, making it possible to suppress the reflection of radio waves at the interfaces between the first glass plate 11 and the first interlayer film 31 and between the second glass plate 12 and the first interlayer film 31. The values of Γ1 and Γ2 at this time are the same as those in FIG.
[0107] Next, the simulation results shown in Fig. 10, that is, the relative dielectric constant of the intermediate film is ε m1 ≧6.72 (excluding Comparative Examples 1 and 2). As shown in FIG. 10, when the relative dielectric constant of the first intermediate film 31 is ε m1 In Comparative Examples 1 and 2, where the relative dielectric constant ε m1 The radio wave reflection characteristics were also high even when the relative dielectric constant ε of the first intermediate film 31 was in the range of 18 (Comparative Example 3) to 20 (Comparative Example 4). m1 The radio wave reflection characteristics improved (deteriorated) as the relative dielectric constant of the first intermediate film 31 decreased in the order of ε m1 The radio wave reflection characteristics were the lowest when = 6.72.
[0108] In other words, the relative dielectric constant of the first intermediate film 31 is ε m1 = 6.72, the relative dielectric constant of the first intermediate film 31 approaches the relative dielectric constant (6.72) of the first glass sheet 11 and the second glass sheet 12. m1 = 6.72, the difference in relative dielectric constant between the first glass plate 11 and the first interlayer film 31 and the difference in relative dielectric constant between the second glass plate 12 and the first interlayer film 31 become small, making it possible to suppress the reflection of radio waves at the interfaces between the first glass plate 11 and the first interlayer film 31 and between the second glass plate 12 and the first interlayer film 31. The values of Γ1 and Γ2 at this time are the same as in the case of FIG.
[0109] Considering the simulation results of the radio wave transmission characteristics shown in FIG. 7 and the simulation results of the radio wave reflection characteristics shown in FIG. 9, the relative dielectric constant of the first intermediate film 31 is ε m1 In the range of ≦6.72, the relative dielectric constant ε of the first intermediate film 31 m1When the refractive index is 3 or more, preferably 3.5 or more, more preferably 4.5 or more, and even more preferably 5.5 or more, the transmittance of millimeter wave band radio waves can be increased.
[0110] In addition, considering the simulation results of the radio wave transmission characteristics shown in FIG. 8 and the simulation results of the radio wave reflection characteristics shown in FIG. 10, the relative dielectric constant of the first intermediate film 31 is ε m1 In the range of 6.72 or more, the relative dielectric constant ε of the first intermediate film 31 m1 When it is 15 or less, preferably 13 or less, more preferably 10 or less, and further preferably 8 or less, the transmittance of radio waves in the millimeter wave band can be increased.
[0111] FIG. 11 shows the relative dielectric constant ε m1 11 is a graph showing the simulation results of the radio wave transmission characteristics of the laminated glass 1 for incident angles θ of radio waves to the laminated glass 1 of 0°, 30°, 45°, and 60°.
[0112] In the simulation shown in FIG. 11, the relative dielectric constant ε m1 was set to 2.45, 3, 5, 6.72, 10, 14, 16, and 18. The relative dielectric constant of the first glass plate 11 was set to ε g1 = 6.72, and the relative dielectric constant of the second glass plate 12 is ε g2 = 6.72. Each dielectric constant is a dielectric constant at a frequency F = 79 GHz. The thickness of each of the first glass plate 11 and the second glass plate 12 was 2 mm, and the thickness of the first interlayer film 31 was 0.76 mm. The frequency range in the simulation was 70 GHz to 84 GHz, and the average value of the radio wave transmission characteristics in this frequency range was plotted on a graph. The incident angle θ of the radio wave to the laminated glass 1 was 0°, 30°, 45°, and 60°.
[0113] As shown in FIG. 11, when the incident angle θ of the radio wave to the laminated glass 1 is 0°, the relative dielectric constant of the first interlayer 31 is ε m1 = 3, ε m1On the other hand, when the relative dielectric constant of the first intermediate film 31 was ε m1 = 6.72, ε m1 When the incident angle θ of the radio wave to the laminated glass 1 is 30°, the relative dielectric constant of the first interlayer 31 is ε m1 = 5, ε m1 On the other hand, when the relative dielectric constant of the first intermediate film 31 was ε m1 = 2.45, ε m1 When = 18, the radio wave transmission characteristic was low.
[0114] When the incident angle θ of the radio wave to the laminated glass 1 is 45°, the relative dielectric constant of the first interlayer 31 is ε m1 On the other hand, when the relative dielectric constant of the first intermediate film 31 was ε m1 = 2.45, ε m1 When the incident angle θ of the radio wave to the laminated glass 1 is 60°, the relative dielectric constant of the first interlayer 31 is ε m1 On the other hand, when the relative dielectric constant of the first intermediate film 31 was ε m1 = 2.45, ε m1 When = 18, the radio wave transmission characteristic was low.
[0115] 11, the larger the incident angle θ of the radio wave on the laminated glass 1, the higher the radio wave transmission characteristics. When the incident angle θ of the radio wave on the laminated glass 1 is 0°, the relative dielectric constant of the first interlayer 31 is ε m1 = 6.72, the value of the radio wave transmission characteristic decreased, but as the incident angle θ of the radio wave to the laminated glass 1 became 30°, 45°, and 60°, ε m1 The decrease in the value of the radio wave transmission characteristic when = 6.72 has been mitigated.
[0116] 12 and 13 are diagrams showing simulation results of the radio wave transmission characteristics of the laminated glass 1. Fig. 12 shows the simulation results when the incident angle θ of the radio wave to the laminated glass 1 is 0° to 30°, and Fig. 12 shows the simulation results when the incident angle θ of the radio wave to the laminated glass 1 is 40° to 67.5°.
[0117] In the simulations shown in Figs. 12 and 13, the relative dielectric constant ε m1 was 6.15, and the relative dielectric constant ε m1 The relative dielectric constant of the first glass plate 11 was set to ε g1 = 6.72, and the relative dielectric constant of the second glass plate 12 is ε g2 = 6.72. Each dielectric constant is a dielectric constant at a frequency F of 79 GHz. The thickness of each of the first glass plate 11 and the second glass plate 12 was 2 mm, and the thickness of the first intermediate film 31 was 0.76 mm. The frequency range in the simulation was 64 GHz to 90 GHz.
[0118] As shown in Figs. 12 and 13, in the comparative example, when the incident angle θ of the radio wave to the laminated glass 1 was 0° to 50°, the radio wave transmission characteristics were low and took a minimum value in the range of 66 GHz to 74 GHz. In contrast, in the laminated glass 1 according to the embodiment of the present invention (Example 1), when the incident angle θ of the radio wave to the laminated glass 1 was in the range of 0° to 67.5°, the radio wave transmission characteristics were not extremely decreased, and compared to Comparative Examples 1 and 2, the radio wave transmission characteristics were stable in the range of 64 GHz to 90 GHz. In addition, in the laminated glass 1 according to the embodiment of the present invention (Example 1), the fluctuation of the radio wave transmission characteristics due to frequency became smaller as the incident angle θ of the radio wave to the laminated glass 1 increased. In addition, the laminated glass 1 according to the embodiment of the present invention (Example 1) showed a higher value of the radio wave transmission characteristics overall compared to Comparative Examples 1 and 2. In particular, when the incident angle θ of the radio wave to the laminated glass 1 was 60° or more, the value of the radio wave transmission characteristics of the laminated glass 1 according to the embodiment of the present invention (Example 1) was higher than those of Comparative Examples 1 and 2 in the entire range of 64 GHz to 90 GHz.
[0119] (Examples 2 to 13, Comparative Examples 1 to 4) Next, for each of the glasses of Composition Examples 1 to 5 shown in Table 1, five combinations of the first glass plate 11 and the second glass plate 12 and three types of materials for the first interlayer film 31 were prepared, and a total of 15 types of laminated glass were examined. Specifically, for each of the Examples and Comparative Examples, the results when a radio wave of 79 GHz was incident at an incident angle θ=67.5° were obtained by simulation. At this time, the thicknesses of the first glass plate 11 and the second glass plate 12 were all 2 mm, and the thickness of the first interlayer film 31 was all 0.76 mm. Note that Comparative Examples 1 and 2 are the same as the laminated glasses of Comparative Examples 1 and 2 described above. Furthermore, the first interlayer film 31 in each of the Examples and Comparative Examples had a relative dielectric constant ε at 79 GHz based on the measured value of the relative dielectric constant at 10 GHz. m1 We estimated the following.
[0120] [Table 2]
[0121] In the laminated glasses of Comparative Examples 1 to 4 and Examples 2 to 3, the first interlayer film 31 was made of PVB(ε m1=2.45) was used. In the laminated glasses of Examples 4 to 8, the first interlayer film 31 was prepared by mixing (dry blending) the glass powder (particle size 100 μm or less) shown in "Composition Example 1" in Table 1 with the matrix resin PVB, with the volume content adjusted to be within the range of 1 vol% to 50 vol%. Furthermore, in the laminated glasses of Examples 9 to 13, the first interlayer film 31 was prepared by mixing (dry blending) the barium titanate (BaTiO3) powder with a particle size of 1 μm or less with the matrix resin PVB, with the volume content adjusted to be within the range of 1 vol% to 50 vol%. Then, this mixture was put into a resin melt twin-screw kneader (Labo Plastomill manufactured by Toyo Seiki Seisakusho), and melt-kneaded under the conditions of a kneading temperature of 160°C, a screw rotation speed of 50 rpm, and a kneading time of 3 minutes to obtain a composite sample. This composite sample was press molded at 160° C. using a hot press machine (Mini Test Press manufactured by Toyo Seiki Seisakusho) to obtain a sheet with a thickness of 0.4 mm, and the relative dielectric constant and dielectric loss tangent were measured by the above-mentioned SPDR method.
[0122] From the results in Table 2, it was confirmed that in Examples 2 to 13, the smaller Γ1 was, the larger S21 was, and the radio wave transmission was good. In addition, when Γ1 was 0.05 or less and the relative dielectric constants (ε g1 ,ε g2 ,ε m1 Example 13, in which the dielectric loss tangent (tan δ at 79 GHz) of the first glass plate 11 and the second glass plate 12 was 0.018 or less, showed the best S21 value.
[0123] In the above embodiment, the first interlayer film 31 has a single layer structure. However, in the present invention, the first interlayer film 31 may further include other layers. For example, in the present invention, the interlayer film 13 (the first interlayer film 31 or the first interlayer film 31 and the second interlayer film 32) may further include a sound insulation layer. The sound insulation layer has a three-layer structure, for example, including a first skin layer and a second skin layer on both sides of the core layer. The sound insulation can be maintained by making the elastic modulus of the core layer smaller than the elastic modulus of the first skin layer and the second skin layer. The elastic modulus is the value of the storage elastic modulus when a frequency dispersion measurement is performed at a strain of 0.05% using a dynamic viscoelasticity measuring device (DMA). In this way, the sound insulation of the laminated glass can be improved by including a sound insulation layer. In the present invention, a black ceramic film may be printed on a part (for example, the peripheral part) of the first glass sheet 11 and the second glass sheet 12. Furthermore, the laminated glass 1 of the present invention may be used as a radome for a millimeter wave radar device.
[0124] While the present invention has been described above in accordance with the above-described embodiment, the present invention is not limited to the configuration of the above-described embodiment, and naturally includes various modifications, alterations, and combinations that may be made by a person skilled in the art within the scope of the invention as defined in the claims of the present application.
[0125] This application claims priority based on Japanese Patent Application No. 2020-013822, filed on January 30, 2020, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]
[0126] 1,1a,1b Laminated glass 10. Housing 11 First glass plate 12 Second Glass Pane 13 Interlayer 21 First area 22 Second area 31 First Interlayer 32 Second Interlayer 100 vehicles
Claims
1. A first glass plate; A second glass plate; an interlayer film sandwiched between the first glass plate and the second glass plate, A predetermined frequency in the range of 60 GHz to 100 GHz is F [GHz], and the relative dielectric constant of the first glass plate at the frequency F is ε g1 , the relative dielectric constant of the second glass plate is ε g2 The relative dielectric constant of the first intermediate film provided in the first region of the intermediate film is ε m1 The reflection coefficient at the interface between the first glass plate and the first interlayer film when light is incident at the frequency F is Γ 1 and the reflection coefficient at the interface between the second glass plate and the first interlayer film is Γ 2 When [0010] and 0.0≦Γ 1 ≦0.2、 0.0≦Γ 2 ≦0.2、 Satisfied, the intermediate film contains at least one selected from the group consisting of polyvinyl butyral, ethylene vinyl acetate, cycloolefin polymer, urethane resin, and polyvinylidene fluoride resin (PVDF); the first intermediate film contains at least one selected from the group consisting of Al2O3, TiO2, SiO2, ZrO2, YSZ, SnO2, forsterite, cordierite, steatite, barium magnesium niobate, barium neodymium titanate, lead zirconate titanate (PZT), borosilicate glass, alkali-free glass, glass fiber, soda-lime glass, phosphate glass, BaTiO3, SrTiO3, BaSrTiO3, aluminum nitride, and MnO2; Laminated glass.
2. In a plan view of the first glass plate, the relative dielectric constant of the first interlayer film at the frequency F is: 0.0≦|e g1 -e m1 | / e g1 ≦0.6、 0.0≦|e g2 -e m1 | / e g2 ≦0.6、 The laminated glass according to claim 1 , which satisfies the above.
3. the interlayer film has the first region and the second region in a plan view of the first glass plate, The relative dielectric constant of the second intermediate film provided in the second region at the frequency F is ε m2 When e m2 ≠e m1 、 and |e g1 -e m2 | / e g1 >0.6、 |e g2 -e m2 | / e g2 >0.6、 The laminated glass according to claim 1 or 2, which satisfies the above.
4. The ε m1 , the ε m2 teeth, e m1 >e m2 、 The laminated glass according to claim 3, which satisfies the above.
5. The ε m1 , the ε m2 teeth, e m1 -e m2 ≧1.5、 The laminated glass according to claim 3 or 4, which satisfies the above.
6. The second intermediate film is made of a material selected from the group consisting of polyvinyl butyral, ethylene vinyl acetate, cycloolefin polymer, urethane resin, fluorine-based resin, fluorine rubber, polyimide resin, liquid crystal polymer, bismaleimide triazine resin, polyphenylene ether, polyether terephthalate, and acrylic resin such as polymethyl methacrylate resin, silicone resin, ABS resin, and Al. 2 O 3 , SiO 2 The laminated glass according to any one of claims 3 to 5, comprising at least one selected from the group consisting of:
7. The ε g1 , the ε g2 , the ε m1 teeth, e g1 -e m1 ≦3.5、 e g2 -e m1 ≦3.5、 The laminated glass according to any one of claims 1 to 6, which satisfies the above.
8. The laminated glass according to any one of claims 1 to 7, wherein the first interlayer film has a visible light transmittance of 70% or more.
9. When a radio wave having the frequency F is incident on the first glass plate at an incident angle θ of 30°≦θ≦90°, the first interlayer film has a m1 But 3≦ε m1 The laminated glass according to any one of claims 1 to 8, which satisfies ≦15.
10. The laminated glass according to any one of claims 1 to 9, wherein the frequency F is 70 GHz to 84 GHz.
11. The first intermediate film is Al 2 O 3 The Al 2 O 3 The laminated glass according to claim 1 , wherein the volume content of is more than 1.8 vol %.
12. The first intermediate film is TiO 2 The TiO 2 The laminated glass according to claim 1, wherein the volume content of
13. The first intermediate film is made of SiO 2 The SiO 2 The laminated glass according to claim 1 , wherein the volume content of
14. The first intermediate film has a composition expressed in mole percentage based on oxides, Yes 2 :50%~85% B 2 O 3 :0%~35% <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :0%~25% Li 2 O+1 2 O+K 2 O:0%~30% MgO: 0% to 15% CaO: 0% to 15% SrO: 0% to 15% BaO: 0% to 15% ZrO 2 :0%~5% TO 2 :0%~10% Fe 2 O 3 :0%~5% SnO 2 :0%~5% 2. The laminated glass according to claim 1, comprising a powdered glass satisfying the above formula (1) and a volume content of the glass being 1 vol % or more and 50 vol % or less.
15. The first intermediate film is a powder of BaTiO 3 The BaTiO 3 The laminated glass according to claim 1, wherein the volume content of
Citation Information
Patent Citations
Glass pane with detector for electromagnetic radiation
JP2011502090A
Glass laminate
JP2019214129A
Window member and vehicle window glass
WO2017188415A1
Window glass
WO2018151235A1